Do age stereotype‐based interventions affect health‐related outcomes in older adults? A systematic review and future directions. Issue 2 (13th July 2021) - Knight, Rachel L.; Chalabaev, Aïna; McNarry, Melitta A.; Mackintosh, Kelly A.; Hudson, Joanne
Abstract : Purpose: Developing interventions that target population‐specific motivational barriers to promote health behaviours is crucial, especially for older adults who are confronted with negative age stereotypes. This systematic review evaluates randomized and non‐randomized field studies that tested the effects of age stereotype‐based interventions on health outcomes in adults aged 50 years and over. Methods: MEDLINE, SPORTDiscus, Scopus, Web of Science Core Collection and PsychINFO were searched to identify articles published up until May 2019. Data were extracted from all articles independently and assessed for risk‐of‐bias using Cochrane Collaboration tools. Results: Ten articles met the inclusion criteria. Health‐related outcome measures were identified across three domains: physical, psychological/psychosocial well‐being, and quality of life/subjective health, with age stereotypes reported as an additional outcome. Intervention structure varied substantially between studies regarding content, duration, frequency, and length of follow‐up. Conclusions: Most studies showed that age stereotype‐based interventions significantly improved physical function or physical activity as well as self‐perceptions of ageing. However, more rigorous studies are needed. Indeed, given the detrimental health effects of age stereotypes, the potential for impact of interventions designed to challenge them is important. Future research should explore the implications of intervening on different stereotype mechanisms, whether intervention effects are comparable across health domains, and whether age stereotype‐based interventions are more effective than non‐age‐specific interventions. PROSPERO Registration CRD42018094006.